PENGOBATAN TERKINI DAN PROFILAKSIS PRIMER PADA TOKSOPLASMOSIS - Reqgi First Trasia (LPPM Universitas Sari Mulia, 2021)
Background: Toxoplasmosis is still a health problem in the world. This parasite is found cosmopolitan in humans and animals. In Indonesia, the prevalence of positive anti-Toxoplasma gondii substances in humans ranges from 2-63%, but there are still few comprehensive studies on current treatment and prophylaxis to treat it. Objective: This article will provide an in-depth review of current treatment and primary prophylaxis in toxoplasmosis. Methods: Searching the latest literature, obtained 10 relevant journals. Results: Initial therapy Pyrimethamine 200 mg was given for 6 weeks. Maintenance therapy (suppressive, secondary prophylaxis) is given for life if immune reconstitution does not occur. Primary prophylaxis against toxoplasmic encephalitis is given to patients who are seropositive for Toxoplasma. Conclusion: Initial therapy, maintenance, and primary prophylaxis can be useful to prevent worsening of the prognosis of toxoplasmosis disease.